Analysis of spatial variability of force detachment of coffee fruits in central pivot - Figueiredo, Vanessa Castro; Ferraz, Gabriel Araújo Silva; Silva, Fabio Moreira da; Conceição, Fagner Goes da; Carvalho, Luis Carlos Cirilo (Coffee Science - ISSN 1984-3909, 2017)
Due to the importance of coffee to the economy of Brazil and the increase of areas even in zone with water deficits during the year, it is necessary to study the factors involved in its production, especially for mechanized and selective harvesting. At this stage coffee farmers find it difficult to determine the appropriate time to start. This research was carried out to evaluating the spatial variation of force detachment of the coffee fruits (green and cherry) under center pivot through geostatistical methods, semivariogram analysis and kriging interpolation, to improve management for harvest mechanical and selective coffee. The test was carried out at Farm Sao Joao Grande, in Presidente Olegario/MG, in a pivot 50.0 ha. The cultivar used was the “Catuai Vermelho IAC 144”, planted in a circular way in December 2000, spaced 4.0 x 0.5 m. The sampling grid was irregular with 100 points georeferenced where each point corresponds to 4 plants. The determination of force detachment was conducted using a digital dynamometer at each sampling point. Within the maturation stages, green fruits presented detachment force greater than the cherry. The semivariogram and kriging allowed to characterize the variability of force detachment between the studied fruits. The kriging maps make it possible to farmers the choice the best place and the right time to start harvest mechanized and selective coffee and consequently, improved final product quality and profits.